Physicochemical properties of a ginkgo seed protein-pectin composite gel. (September 2021) - He, Zhendong; Liu, Changqi; Zhao, Jing; Li, Weiwei; Wang, Yaosong
Abstract: In this study, we investigated the effects of pectin concentrations and degrees of esterification (DE) on the gelling properties of ginkgo seed protein isolate (GSPI) – pectin composite gels. The composite gels were formed by heating a mixture of 12% (w/v) GSPI and pectin (0, 0.1, 0.5, and 1.0% w/v) of different DE (38%, 60%, 76%) at 90 °C, pH 6.0 for 30 min. The addition of pectin increased the apparent viscosity and charge density of the sols while decreased the particle size. Rheological and textural properties of the gels were enhanced by 0.1% and 0.5% of pectin, while 1.0% of pectin led to a poor gel texture, as well as lowed water holding capacity. Changes in gel microstructure were observed when pectins were added. Hydrogen bonds played an important role in gel formation. The addition of low-methoxyl pectin (DE = 38%) with high charge density resulted in superior gelling properties. We demonstrated the potential of a GSPI-pectin composite gel with controllable gelling properties by adjusting the concentration and DE of the pectin. Graphical abstract: Image 1 Highlights: Ginkgo seed protein isolate-pectin hydrogel was fabricated by heat-induced gelation. Pectin concentration as well as esterification degree of pectin determined the properties of complex. Low-methoxyl pectin performed better than high-methoxyl pectin in a protein gel. Complex gel exhibited the variation in the functional properties.